EXPRESSION OF GROWTH HORMONE RECEPTOR GENE ON BALI CATTLE AND WAGYU CATTLE MUSCLE - Suwiti, Ni Ketut; Sudipa, Putu Henrywaesa; Setiasih, Ni Luh Eka (Buletin Veteriner Udayana, 2022)
This study aims to study the molecular weight and distribution of protein growth hormone receptors (GHR). The sample used was the Balinese beef eye ribs and Wagyu beef muscle. Molecular weight examination using the SDS-PAGE receptor method, Western Blotting, and immunohistochemistry staining. The results showed that the weight of the growth hormone receptor protein was 76 Kdalton in both types of cattle and the average score of IHK for Wagyu beef muscle was 234.5 and in Bali cattle was 199.6. It can be concluded, namely the weight molecule of the growth hormone receptor muscle ribs in both Wagyu and bali cattle with equal distribution.